Tracing the value of traceability : Identifying the value of traceability within textile and apparel value chains - Ervast, Maria (My University, 2024)
In recent years, the global landscape of the textile and apparel industry has undergone a profound transformation, primarily driven by escalating environmental and social concerns related to prevalent fast fashion models, unsustainable consumption practices, and misleading green certifications. The industry faces exacerbated challenges due to excessive consumption and rapid production, leading to intensified social issues within complex and globally interconnected value chains. The lack of transparency in these complex networks has spurred various stakeholders, including consumers, suppliers, regulators, and policymakers, to advocate for heightened transparency and access to traceability data. Recognizing the need for greater value chain resilience in the face of an increasingly volatile business landscape, companies grapple with the urgency for traceability, which, despite being evident, faces a gap in widespread implementation This study centres on the theme of value creation through traceability within textile and apparel value chains, with a specific focus on discerning key drivers for traceability, understanding the intricate flow of traceability data, and establishing robust connections between traceability and business objectives. Understanding the facets that contribute value through traceability is crucial, as companies are unlikely to adopt complex practices unless provided with clear explanations of how they can enhance their ability to create value for the organization, specifying the unique value generated for their circumstances. The research employed qualitative methods, employing open-ended, semi-structured interviews with sixteen stakeholders representing companies operating within the textile and apparel value chain. The findings are consistent with existing literature, emphasizing regulatory drivers as primary in traceability implementation. European companies are noted for their advanced practices and sense of urgency in preparing for upcoming regulatory initiatives. Traceability emerges as a strategic tool to mitigate risks, offering visibility into external risks in supply chain management and enhancing understanding of social, environmental, and governmental impacts. It facilitates informed decision-making, supports growth, and unlocks new business opportunities. Additionally, traceability enables access to tax benefits, grants, and opportunities for adjusting the pricing of traced products. It serves as a tool for coherent and verified storytelling, meeting consumer demands for sustainability and circularity matters. The study's insights offer guidance for companies operating within textile and apparel value chains, aiding them in formulating a traceability strategy that focuses on engaging in traceability practices that generate value. Using the commissioning company as an illustrative example, the study provides valuable insights into key drivers for traceability and tools to facilitate effective traceability data flow, thereby enhancing value across stakeholders in the value chain.

Maailman tekstiili- ja vaatetusteollisuus on kokenut merkittävää muutosta viime vuosina. Tähän ovat ajaneet kasvavat ympäristölliset ja sosiaaliset huolenaiheet, jotka liittyvät vallitseviin pikamuotimalleihin, kestämättömiin kulutustottumuksiin ja harhaanjohtaviin vihreisiin sertifikaatteihin. Teollisuus kohtaa entistä suurempia haasteita ylenmääräisen kulutuksen ja nopean tuotannon vuoksi, mikä on johtanut monimutkaisten ja globaalien arvoketjujen sisällä voimistuviin sosiaalisiin ongelmiin. Monimutkaisten verkostojen läpinäkyvyyden puute on kannustanut eri sidosryhmiä, mukaan lukien kuluttajia, toimittajia, sääntelijöitä ja päättäjiä, vahvistamaan läpinäkyvyyttä ja jäljitettävyyttä alalla. Jäljitettävyyden vahvistamisen ja käyttöönoton pyrkimyksissä on kuitenkin huomioitava, että sen toteuttamiseen liittyy haasteita. Tämä tutkimus keskittyy arvon luomisen teemaan, fokuksena jäljitettävyys tekstiili- ja vaatearvoketjuissa. Tutkimuksessa perehdytään erityisesti avainajureiden tunnistamiseen, jäljitettävyyden tietovirtojen fasilitoinnin jäsentelyyn sekä yhteyksien luomiseen jäljitettävyyden ja liiketoimintatavoitteiden välille. Jäljitettävyyden avulla lisäarvoa tuovien näkökohtien ymmärtäminen on ratkaisevan tärkeää, sillä yritykset eivät mitä todennäköisemmin ota käyttöön sellaisia monimutkaisia käytäntöjä, joiden avulla ei voida selittää organisaatiolle saatavaa merkityksellistä arvoa. Tutkimuksessa käytettiin laadullisina menetelminä avoimia puolistrukturoituja haastatteluja, joissa oli mukana kuusitoista eri tekstiili- ja vaatetearvoketjussa toimivan yrityksen edustajia. Tutkimuksen tulokset ovat linjassa olemassa olevan kirjallisuuden kanssa, korostaen regulaattorisia ajureita ensisijaisina kannustajina jäljitettävyyden toteuttamisessa. Eurooppalaiset yritykset saivat tunnustusta edistyneistä käytännöistään ja proaktiivisesta asenteesta valmistautua tuleviin sääntelytoimiin. Jäljitettävyys näyttäytyy strategisena työkaluna riskien lieventämisessä, tarjoten samalla näkyvyyttä ulkoisiin riskeihin toimitusketjun hallinnassa sekä lisäten ymmärrystä sosiaalisista, ympäristöllisistä ja hallinnollisista vaikutuksista. Jäljitettävyys helpottaa informoitujen päätösten tekemistä, tukee kasvua ja avaa uusia liiketoimintamahdollisuuksia. Lisäksi jäljitettävyys mahdollistaa pääsyn verohyötyihin, avustuksiin ja mahdollisuuksiin säätää jäljitettyjen tuotteiden hintoja. Se toimii työkaluna johdonmukaiseen ja todennettuun tarinankerrontaan, vastaten kuluttajien vaatimuksiin kestävyyden ja kiertotalousajattelun toteutumisesta. Tutkimuksen löydökset tarjoavat ohjausta tekstiili- ja vaatearvoketjuissa toimiville yrityksille, auttaen niitä muotoilemaan jäljitettävyysstrategiaa, joka keskittyy osallistumaan jäljitettävyyteen arvoa tuottavilla tavoilla. Havainnollisena esimerkkinä käytetty toimeksiantajayritys tarjoaa arvokkaita oivalluksia jäljitettävyyden avainajureista sekä työkaluista, jotka helpottavat tehokasta jäljitettävyyden tietovirran kulkua, siten lisäten arvoa arvoketjun sidosryhmille.
Keywords: Traceability, textile and apparel industry, value chain, value creation, risk management